Labour Regulation and Development Socio-Legal Perspectives - Marshall, Shelley; Fenwick, Colin (Edward Elgar Publishing, 2016)
This book is an exploration of arguments about the economic and social effects of the regulation of labour, and whether it is likely to be helpful or harmful to development. Authored by contributors from a variety of fields, primarily legal as well as development studies, economics and regulatory studies, the book presents both empirical and theoretical analyses of the issues. With authors from several continents, this collection is unique in that it focuses on labour regulation in poor and middle-income countries rather than industrialised ones, therefore making it a significant contribution to the field. In large part, the authors conclude that regulation of labour can play a positive role in promoting social and economic development, especially over time. Effective regulation has the potential to promote democratic engagement at work and beyond. However, its impact is dependent on how much its design grapples with the particular arrangements of work occurring within different industries, reflecting the nature of development and social relations within that country. Contributors emphasise that regulation needs to be adapted to the challenges presented by non-standard employment relations, changes in the structure of work and the rise of global value chains. This collection's exploration of labour regulation in developing countries will be of interest to labour law scholars and teachers, and to policy-makers in the field of labour regulation - especially in the global South - as well as to technical advisers and those engaged in the practice of industrial relations.